2012
DOI: 10.1590/s0104-07072012000400008
|View full text |Cite
|
Sign up to set email alerts
|

As inter-relações da rede social do homem com câncer na perspectiva bioecológica: contribuições para a enfermagem

Abstract: ABSTRACT:It has the objective of knowing the characteristics of the social network inter-relations of the man with cancer, in chemotherapeutic treatment. Qualitative study that used as theoretical referential the Bioecological model by Bronfenbrenner and the Ecological Insertion method. Three men with cancer participated, and they were attended in a chemotherapeutic service between April and September 2010. It was performed an average of six meetings with each subject. The interviews data were submitted to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
(35 reference statements)
0
3
0
3
Order By: Relevance
“…This is because, it was observed that the relationships established by men are given mainly to people with whom they have close contact, and the family members stand out in this context. If necessary, having someone to seek support promotes relief and safety for man and using communication makes him feel comfortable and empowered, in situations of suffering or not (6) . Facing that, talking represents a communicative process, synonymous of help, attention, sharing and reinvigoration of positive relationships for health (7) , and to confirm that the socialization of this issue in many occasions, combats invisibility and male passivity facing health.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is because, it was observed that the relationships established by men are given mainly to people with whom they have close contact, and the family members stand out in this context. If necessary, having someone to seek support promotes relief and safety for man and using communication makes him feel comfortable and empowered, in situations of suffering or not (6) . Facing that, talking represents a communicative process, synonymous of help, attention, sharing and reinvigoration of positive relationships for health (7) , and to confirm that the socialization of this issue in many occasions, combats invisibility and male passivity facing health.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, health professionals should be alert to the identification of this support network and take advantage of different opportunities to establish contact with men, thus reinforcing the importance of healthy relationships and establishing new contacts for health (6) . However, when the subject does not build healthy relations, it is also up to the health professional to intervene so that changes in this direction occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esses resultados convergem com investigação realizada com homens com neoplasia, o qual referia o benefício recebido por eles por parte de amigos, de vizinhos e de familiares, na ajuda quanto à locomoção e quanto ao suporte financeiro. Esses auxílios foram fundamentais para o enfrentamento do adoecimento, promovendo aos familiares a esperança de apostar na recuperação 19 .…”
unclassified
“…O apoio emocional pode ser equiparado com o "estar lá"; a companhia social, por sua vez, caracteriza-se pelo vivenciar momentos juntos 2 , ou "estar presente". A presença, no momento do sofrimento, não precisa ser física, pois o apoio pode ultrapassar tais barreiras e ser ofertado pelos próprios integrantes da família 19,20 .…”
unclassified